Sustainable meaningful learning through the tree of knowledge: a teaching project for Nepal - Pérez de Villarreal Zufiaurre, Maider (European Public & Social Innovation Review, 2024)
Introduction: The climate crisis and social justice are at the focus of UNESCO's 2030 Agenda, which presents 17 SDGs (Sustainable Development Goals) as a roadmap for the preservation of the planet. From the educational field, its achievement can be promoted through the design of educational projects that promote sustainable meaningful learning (SML) hand in hand with learning for social justice (LSJ). In this context, an innovative teaching practice was developed in 2021-22 using biosphere reserves in Nepal, in which students from the International Primary Education Teacher Degree Program designed teaching materials to be offered to nearby primary schools in Nepal, close to the selected biosphere reserve. Methodology: The students built knowledge models based on conceptual maps about the selected biosphere reserve, creating teaching units with activities aimed at students in Nepal. A tree of knowledge was also designed that summarized the joint project as a metacognitive tool for sustainable meaningful learning. Results: For the evaluation, a double rubric was used that analysed both the oral defence of the project and the different sections of the UD, and personal reflections were analysed, as well as the learning results and motivation. Discussion: Sustainable meaningful learning together with learning for social justice and the didactic tools that were used are very valid methodologies to stimulate international cooperation and promote meaningful, autonomous, motivating and sustainable learning.